2019
DOI: 10.1016/j.neuroimage.2018.10.076
|View full text |Cite
|
Sign up to set email alerts
|

High frequency repetitive transcranial magnetic stimulation to the left dorsolateral prefrontal cortex modulates sensorimotor cortex function in the transition to sustained muscle pain

Abstract: 2019) High frequency repetitive transcranial magnetic stimulation to the left dorsolateral prefrontal cortex modulates sensorimotor cortex function in the transition to sustained muscle pain. NeuroImage,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 74 publications
4
29
4
Order By: Relevance
“…Moreover, previous research in healthy pain-free individuals demonstrated that network-tDCS (Fischer et al, 2017), bilateral M1 tDCS (Maezawa et al, 2019), single-site M1 tDCS (Nitsche et al, 2005) and repeated-TMS (rTMS) to M1 increased corticomotor excitability above baseline values. Results are also in agreement with rTMS studies in experimental pain (De Martino et al, 2019;Fierro et al, 2010) and chronic disorders (De Andrade et al, 2011;Mhalla et al, 2011;Moisset et al, 2016) where pain-related changes in corticomotor excitability were reverted to normal levels, but not beyond them, when targeting DLPFC or M1. These pieces of evidence suggest that tDCS effects on the corticomotor excitability show a state dependency (i.e.…”
Section: Counteraction Of Pain-related Corticomotor Inhibition After Network-tdcssupporting
confidence: 88%
“…Moreover, previous research in healthy pain-free individuals demonstrated that network-tDCS (Fischer et al, 2017), bilateral M1 tDCS (Maezawa et al, 2019), single-site M1 tDCS (Nitsche et al, 2005) and repeated-TMS (rTMS) to M1 increased corticomotor excitability above baseline values. Results are also in agreement with rTMS studies in experimental pain (De Martino et al, 2019;Fierro et al, 2010) and chronic disorders (De Andrade et al, 2011;Mhalla et al, 2011;Moisset et al, 2016) where pain-related changes in corticomotor excitability were reverted to normal levels, but not beyond them, when targeting DLPFC or M1. These pieces of evidence suggest that tDCS effects on the corticomotor excitability show a state dependency (i.e.…”
Section: Counteraction Of Pain-related Corticomotor Inhibition After Network-tdcssupporting
confidence: 88%
“…The DLPFC is involved in many cognitive and regulatory functions and connected to different functional brain networks (Seminowicz & Moayedi, ). Regarding tonic experimental pain, modulatory effects of the DLPFC on the excitability of the sensorimotor cortex were reported (De Martino, Seminowicz, Schabrun, Petrini, & Graven‐Nielsen, ). The present observation of increased connectivity between sensorimotor and lateral prefrontal cortex would be, in principle, well compatible with these observations of an important role of dorsolateral prefrontal‐sensorimotor connectivity in tonic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our findings that suggest decreased corticomotor excitability direct oppose the vicious cycle theory (Travell et al, ). Nonetheless, recent studies have presented the opposite effect for the spinal innervation, i.e., increased corticomotor excitability following repeated injections of NFG into the extensor carpi radialis brevis (ECRB), which is likely explained as a motor learning effect that results from the search for a new moment strategy in the affected limb (De Martino, Seminowicz, Schabrun, Petrini, & Graven‐Nielsen, ; De Martino, Zandalasini, Schabrun, Petrini, & Graven‐Nielsen, ; Schabrun, Christensen, Mrachacz‐Kersting, & Graven‐Nielsen, ). There are some important methodological differences that could account for these contradictory findings, besides the need of the above‐mentioned pre‐activation level: (a) the tonic muscle contractions could have facilitated nociceptive inputs in the NGF injected masseter.…”
Section: Discussionmentioning
confidence: 99%